Socioeducational needs for children in Bilbao: a cross look from the territory - Rosa Santibañez Gruber; Teresa Laespada Martínez (Sociedad Iberoamericana de Pedagogía Social, 2016)
The presented paper is part of a larger project that has developed three studies on the situation of the program Caixa ProInfancia CPI in the ten territories where it was implemented: the first on child poverty mapping in each of the cities or territories, its relationship with public resources as well as the presence and intensity of CPI; the second about the perception of the CPI impact on families, children and professionals' programs; and the third, 3 depth cases of study at every city on the program perception and impact. This paper's main goal is to present the process of research carried out in the first mapping study of child poverty in Bilbao which starting from the analysis of the demographic and social data of the city, proposes the application of the principles set out in international and regional policies adjusting them to the local situation.  The study is developed using a quantitative methodology based on secondary sources, with the aim of developing a descriptive report of CPI programme entities situation in Bilbao, contextualizing its work to the social situation of the city and in relation to the services offered by the public administration, and mainly by the City Council of Bilbao. The district is used as a territorial unit of analysis and subsequent intervention, in order to assess the risk level. In addition, it progresses in the subsequent decisions based on this analysis of reality, creating a selection criteria or ranking of priority territories and launching collaborative community work and network-based pilot projects. It is concluded improvement and innovation processes in this field necessarily require a systematic and contextual evaluation with greater participation and networking.